HYBRID MODULATION TECHNIQUE TO IMPROVE RECEIVER SENSITIVITY FOR FSO LINK PROPAGATION - S. A., Kwang Thai; Abdul Rahman, Kram; Khairul Fikri, Tamrin; Rosdisham, Endut; Siti Kudnie, Sahari (Little Lion Scientific, 2024)
Free space optical (FSO) communication is now become a main communication due to the ability of propagation channel to operate up to Terabit per sec (Tbs) and can support high number user. The FSO suffer when experience severe weather condition. Apart from that FSO also facing threshold problem especially related with Amplitude Shift Keying - Onn Off Keying (ASK-OOK) when dealing poor signal and the biggest effect is high noise presence at receiver which led the signal to deteriorate. In this research proposed new development of transmitter and receiver design in order to reduce the impact of atmospheric attenuation and increase receiver sensitivity. In this paper focus on the analysis performance related bit rate which will compare with conventional amplitude shift keying (ASK) approach. Simulation result will be used to measure the performance and comparison between conventional and new proposed modulation double transmission balance receiver (DTBR) will also be presented. It was anticipated that proposed technique which offer a simple and inexpensive procedure capable of increasing received power, receiver sensitivity, and decreasing bit error rate would be used. The measurement of result will involve the effect of geometrical loss, data bit rate and distance propagation. Four level of synchronous transport module (STM) which is STM1(155Mbps), STM4(622Mbps), STM16(2.5Gbps) and STM64(10Gbps) will be compare the performance of bit rate. Meanwhile two different distances will test to measure the ability system extend the range transmission. From the result, the DTBR can increase 25% improvement as compare to conventional ASK.